'Philosophising with Athletes and Their Coaches': On Using Philosophical Thinking and Dialogue in Sport. Issue 2 (3rd April 2023) - Mareš, Lukáš
ABSTRACT: Philosophy may be accused of being an exclusive theoretical enterprise. Although it is concerned with the important issues of life it may appear to be a purely academic matter pursued by few educated scholars and therefore somehow detached from everyday way of being of people uneducated in philosophy. In the field of the philosophy of sport, the essential ambition is to provide relevant insights into a vast area of sport that will promote our philosophical understanding and knowledge of the relevant topics. This paper offers another perspective on the role of philosophy in sport. I argue that philosophy is not just about reflecting from an academic distance, but the process of philosophizing could be situated within the sporting practices. This type of relationship between philosophy and sport is already apparent in ancient Greece where philosophers (such as Pythagoras or Socrates) liked to be engaged in physical exercises and to combine them with philosophical discussions with athletes. The article explores a practical role of philosophy in sport, namely the process of philosophical thinking and dialogue with athletes and their coaches. It offers insights into methodology, goals, benefits, and limits of using philosophy in practice. I reflect on my personal experience of being a mental coach and philosophical consultant in sport in the Czech Republic. The aim of this article is to demonstrate the relevance of using philosophy (philosophical practice) in the sporting environment. In doing so, I reflect on the nature and purpose of philosophical thinking and its possible relation to sport psychology and mental coaching.